2020
DOI: 10.3390/diagnostics10110941
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Release, Clinical and Radiological Outcomes in Large Diameter Metal-on-Metal Total Hip Arthroplasty at Long-Term Follow-Up

Abstract: Total hip arthroplasty (THA) with metal-on-metal (MoM) bearings have shown problems of biocompatibility linked to metal ion release at the local level causing an adverse reaction to metal debris (ARMD) and at a systemic level. The aim of this study was to evaluate clinical and radiological outcomes, and metal ion concentrations in the blood and urine of patients who underwent THA with the LIMA Met-Met hip system. Patients with ceramic-on-ceramic (CoC) bearings were included as a control group. In this study, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“… 65 Many factors may negatively impact this wear process and increase the metal ion release or lead to higher metal ion levels as suboptimal surgical positioning of the implant, 66 impaired renal function and bilateral hip replacement, 67 and mixing components from different manufacturers or different types. 68 The current work showed that age does not correlate to the blood ions levels in accordance with Pozzuoli et al 15 In addition, the ion levels showed a non-significant difference between males and females in contrast to Delaunay et al 69 who reported that female sex seems to be significantly associated with higher circulating metal ions secondary to variations in the metabolism of metal ions. The variability between this study and the current work can be related to the difference in the type of implant.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 65 Many factors may negatively impact this wear process and increase the metal ion release or lead to higher metal ion levels as suboptimal surgical positioning of the implant, 66 impaired renal function and bilateral hip replacement, 67 and mixing components from different manufacturers or different types. 68 The current work showed that age does not correlate to the blood ions levels in accordance with Pozzuoli et al 15 In addition, the ion levels showed a non-significant difference between males and females in contrast to Delaunay et al 69 who reported that female sex seems to be significantly associated with higher circulating metal ions secondary to variations in the metabolism of metal ions. The variability between this study and the current work can be related to the difference in the type of implant.…”
Section: Discussionsupporting
confidence: 86%
“…12 However, any metal surrounded by biological systems will corrode, leading to the release of metal ions that cause adverse physiological effects including toxicity, and metal allergy. 13,14 Although the majority of cases of hypersensitivity reactions attributed to corrosion products and elevation of cobalt and chromium ions in the blood were reported in metal-onmetal (MOM) implants, [15][16][17] these reactions have been also reported in the metal-on-polyethylene patients. 18 Although Bijukumar et al 19 showed that the metal wear rate of MOM articulation is approximately 20 times lower than that of MOP articulation, the polyethylene particle wear is reduced in the recently introduced highly cross-linked polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Pozzuoli et al [ 31 ] , were able to perform a 7-year follow-up, from which they reported a revision-rate for MOM prostheses where they conducted clinical and radiographic evaluations in relation to metal-ion release[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to these bearings using local materials that are easily available, the ease of the fabrication process, and the relatively affordable cost compared to other bearings. Unfortunately, several complications from metal-on-metal cause considerations that require choosing another bearing for total hip prosthesis [ 2 ]. This is also supported by the statement of the Australian Orthopaedic Association (AOA) [ 3 ], which explains the case of metal-on-metal failure is relatively high compared to the other bearing options available in the market today.…”
Section: Introductionmentioning
confidence: 99%